2006
DOI: 10.1007/s10877-006-9052-x
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity-Based Hematocrit Measurement During Cardiopulmonary Bypass

Abstract: Conductivity-based POC hematocrit measurement suffers from biases due to changes of the plasma constituents. The downward bias in hematocrit as often seen during cardiopulmonary bypass is driven by changes of different electrolyte concentration rather than by colloids used per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Treatment of anemia based on clinical judgment would, therefore, result in a large number of unnecessary transfusions compared with a protocol guided by point-of-care testing. Previous studies in the context of cardiopulmonary bypass surgery have found systematic errors caused by alterations in plasma proteins and electrolytes from the conductivity-based i-STAT measurement compared with reference methods 12,21 ; however, our patients were managed with cautious administration of fluids and electrolytes, 22 such that no significant bias was observed. Variability reported in previous studies (±20 g/L) seems to be lower than in our study, perhaps related to the tightly regulated artificial conditions used for testing.…”
mentioning
confidence: 69%
“…Treatment of anemia based on clinical judgment would, therefore, result in a large number of unnecessary transfusions compared with a protocol guided by point-of-care testing. Previous studies in the context of cardiopulmonary bypass surgery have found systematic errors caused by alterations in plasma proteins and electrolytes from the conductivity-based i-STAT measurement compared with reference methods 12,21 ; however, our patients were managed with cautious administration of fluids and electrolytes, 22 such that no significant bias was observed. Variability reported in previous studies (±20 g/L) seems to be lower than in our study, perhaps related to the tightly regulated artificial conditions used for testing.…”
mentioning
confidence: 69%
“…Point-of-care testing has gained special favor in emergency transport systems, critical care departments, and cardiothoracic surgical departments, as is shown by the large volume of systems developed for all of these areas [1214]. …”
Section: Discussionmentioning
confidence: 99%
“…The GEM Premier 3500, which is used for POC ABGA in operating rooms, measures Hct by its conductivity; a small amount of a whole blood sample (135 ml) is tested via aspiration within the disposable cartridge that comprises testing reagent and minimized sensor, and the entire test takes about 85 seconds, which is a shorter length of time than the laboratory test [8]. The Hb/Hct is measured via the following principle: when a low-frequency current is incurred on the blood sample, the non-conductive cell membranes of red blood cells cannot conduct the current, meaning that a higher number of red blood cells results in a lower conductivity; such difference in conductivities is used to measure the Hb/Hct [2,9]. Again, the entire test requires only a few minutes, which makes POC ABGA useful in situations where simple and quick testing is demanded, such as for patients during a surgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…the Hb test results of conductivity-based POC ABGA [2][3][4]. In fact, the authors of this study compared the Hb/Hct measurements generated by ABGA in the operating room and those measured in the laboratory and found that ABGA performed in an operating room tends to result in lower values.…”
mentioning
confidence: 99%